1998
DOI: 10.1046/j.1365-2672.1998.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of specific bacteriocin-producing lactic acid bacteria by colony hybridization

Abstract: A colony hybridization method for detecting lactic acid bacteria encoding specific bacteriocins was developed. Specific PCR-generated probes were used to detect colonies of pediocin PA-1, lactococcin A, enterocin AS-48, nisin A and lacticin 481 producing strains. The probes were shown to be sensitive and specific for sequences belonging to the structural genes of the respective bacteriocins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 13 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…The methods described by Grunstein and Hogness [20] consists in extracting the DNA from bacterial colonies and to bind it to the Hybond-N nylon membrane in situ [28]. The resulting membrane was successively tested with different probes, obtained by PCR using the species-specific primers (Table 1) for reference strains Lactobacillus paracasei DSM 5622 T , Lact.…”
Section: Colony Hybridization Analysismentioning
confidence: 99%
“…The methods described by Grunstein and Hogness [20] consists in extracting the DNA from bacterial colonies and to bind it to the Hybond-N nylon membrane in situ [28]. The resulting membrane was successively tested with different probes, obtained by PCR using the species-specific primers (Table 1) for reference strains Lactobacillus paracasei DSM 5622 T , Lact.…”
Section: Colony Hybridization Analysismentioning
confidence: 99%
“…Genetic methods such as polymerase chain reaction (PCR) (Klijn et al. 1995) and colony hybridization (Martínez et al. 1998) were also attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Bhunia et al (1994) had demonstrated the use of the Southern hybridization technique for the identification of bacteriocin-encoding plasmids. DNA probes have been used earlier to detect silage colonization by Lactobacillus and Pediococcus strains and bacteriocinogenic LAB (Rodriguez et al 1997;Martinez et al 1998). In these studies, the specificity of the DNA probe was tested using pure cultures, but in the present investigation, the pediocin PA-1 probe has been used directly to screen a heterogeneous population of antagonistic cultures isolated from naturally fermented cucumber.…”
Section: Rapid Detection Of Pediocin Producers By Colony Hybridizationmentioning
confidence: 98%
“…Rapid methods such as colony immuno-blot, PCR, gene probe, etc. have been employed that help to overcome these inconveniences (Rodriguez et al 1997;Martinez et al 1998). In the recent past, production of intergeneric and interspecific pediocin PA-1/AcH by Lactobacillus plantarum and P. parvulus has been reported (Ennahar et al 1996;Bennik et al 1997).…”
Section: Introductionmentioning
confidence: 98%